Exploring The Concept of Social Sustainability in Traditional Javanese Settlements in Selopamioro Village, Bantul, Yogyakarta - Diwangkoro, Raden Bagus Budho; Utama, Aditya Noor Hadhy; Handoko, Jarwa Prasetya Sih; Idham, Noor Cholis (Universitas Muhammadiyah Surakarta, 2025)
This study examines the social sustainability of traditional Javanese settlements in Selopamioro Village, Bantul, which maintains its architecture, culture, and natural environment amidst urbanization in Yogyakarta, using descriptive qualitative methods with field observations, in-depth interviews with residents, traditional leaders, and village officials, and secondary document analysis. The results of the study indicate that social sustainability is based on the philosophy of Hamemayu Hayuning Bawana (maintaining human-nature harmony) which is manifested through: (1) minimal high fences (80% of houses) which reflect security based on social capital and communal interaction; (2) pendopo as an inclusive space for access to public services, deliberation, and the economy; and (3) adaptability based on local wisdom, such as conserving teak trees as wedding dowries and building materials. The original contribution of the study lies in the social architecture model that integrates physical design (semi-public space) with community cohesion, as well as the reinterpretation of Javanese philosophy as an operational framework for climate adaptation. These findings offer practical implications for inclusive tourism village planning, culture-based conservation policies (e.g. integration into Village SDGs), and architectural education that emphasizes the principle of